DINAMIKA KEPENTINGAN TIONGKOK DI LAOS GOLDEN TRIANGLE SPECIAL ECONOMIC ZONE DALAM PERSPEKTIF GEOPOLITIK NICHOLAS - Natalie Desta Karunia; Suryo Sakti Hadiwijoyo; Triesanto Romulo Simanjuntak (Bajang Institute, 2025)
This study aims to analyze the dynamics of China’s interest in the Laos Golden Triangle Special Economic Zone (GTSEZ) through the geopolitical perspective of Nicholas Spykman. The development of the Laos GTSEZ in the border area between Thailand, Laos, and Myanmar represent not only an economic project but also a strategic instrument for expanding China’s geopolitical influence in Southeast Asia. This research employs a qualitative method with a descriptive-explanatory approach. The result indicates that the development of the Laos GTSEZ carries a dual dimension, functioning both as an economic project and as a geopolitical instrument. From Spykman’s geopolitical perspective, the Laos GTSEZ reflects China’s strategy to dominate the Southeast Asian rimland as part of its effort to maintain and expand its global influence. Therefore, the establishment of the Laos GTSEZ has implications not only for regional economic growth but also for shifting geopolitical power in Southeast Asia.